Desenvolvimento de uma metodologia para determinação de Cu, Cr e As utilizando microeletrodos - Zimer, Alexsandro Mendes (2005)
Using carbon fiber microelectrode modified with a film of Hg. The employed techniques were differential pulse voltammetry coupled to the adsorptive cathodic stripping for the As and Cr and the differential pulse voltammetry with anodic stripping for the Cu. The film of Hg on carbon fiber was obtained in the potential of -1,2 V (vs. Ag/AgCl) from a mercury nitrate solution 10 mmol L-1 with 1,0 mol L-1 of KNO3 and pH 1,0. The behavior voltammetry of the microelectrodes with and without film of Hg they were tested in potassium hexacianoferrate solution. The metals were analyzed individually in a first stage. In this case the pre-concentration time was of 60 s, in the potentials of -0.7 V for Cu2+ and -0.4 V for As3+ and Cr3+ and the electrolyte was KCl 1.0 mol L-1. Other step involved is the simultaneous determination of these metals, where a pre-concentration was made in -0.4 V by 60 s with cathodic sweep in KCl 1.0 mol L-1. In these experiments it was possible the determination of Cu2+ and of the species As5+. According to the literature As5+ is no eletroactive in the cathodic sweep, being necessary her reduction for detection for electrochemistry techniques. However, in this work a stripping peak was observed, in a cathodic sweep in the potential of -1,2 V, when only this species was added. These results showed that in the studied conditions, the species As5+ can be analyzed by electrochemistry techniques. Other experiments, with the addition of an agent reducer, Na2S2O4 and Cu2+ were performed for the determination of As5+ in the reduced form, in other words, like As3+. The interaction among the species of interest was also evaluated and it was observed that the determination of the pairs of As/Cu and Cr/Cu was possible, but there was interference if As was added with Cr. For all analyzed species, separately or together, the values obtained for the recovery factor, the detection limit and the quantification limit showed that the methodology can be employed in the determination of the species of interest. A test was accomplished for Cu and Ass in wood samples treated with cromated copper arsenate (CCA), and it was obtained a good correlation when it is compared with the results obtained by atomic absorption spectroscopy and pulse polarography techniques.